THE PARTS OF SPEECH: MAIN AND FUNCTIONAL PARTS OF SPEECH IN ENGLISH GRAMMAR (Ustozlar uchun, 2025)
This article examines the concept of parts of speech in English grammar, with particular attention to the distinction between main (content) and functional (minor) parts of speech. The study explains the definition, importance, and historical development of parts of speech, highlighting their grammatical, syntactic, and semantic characteristics. The article also analyzes the functions of nouns, pronouns, verbs, adjectives, adverbs, and functional word classes such as prepositions, conjunctions, articles, particles, and interjections. The findings demonstrate that understanding parts of speech is essential for effective communication, accurate language use, and advanced grammatical analysis.